2011
DOI: 10.1007/s10620-010-1546-1
|View full text |Cite
|
Sign up to set email alerts
|

The Esophageal Multimodal Pain Model: Normal Values and Degree of Sensitization in Healthy Young Male Volunteers

Abstract: Normal values for healthy young men are now provided for the normal and the sensitized state. The percentage of subjects sensitized after acid stimulation are thoroughly documented, and depends on stimulation type and the cut-off value chosen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 43 publications
3
21
1
Order By: Relevance
“…A previous study has demonstrated that the number of participants sensitized to the different modalities is highest for the mechanical stimulation [16]. The present study also demonstrated that participants were sensitized by acid regarding mechanical stimulation but not consistently sensitized to thermal and electrical stimulations.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…A previous study has demonstrated that the number of participants sensitized to the different modalities is highest for the mechanical stimulation [16]. The present study also demonstrated that participants were sensitized by acid regarding mechanical stimulation but not consistently sensitized to thermal and electrical stimulations.…”
Section: Discussionsupporting
confidence: 54%
“…Reproducibility has been proven for the multimodal model in esophagus [14,15]. Additionally, to increase reliability it has been recommended to include a training session before conducting a study where the protocol includes several visits of experimental testing [16]. Moreover, stimulating to the moderate pain threshold seems to be the best approach in studies of analgesic effects [16].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitization to thermal and electrical stimuli, however, was not observed. Interestingly, in a previous study, acid‐induced oesophageal sensitization was observed for thermal as well as electrical stimulation, but the number of participants sensitized to the different modalities was highest for mechanical stimulations (Krarup et al., ). In our study, the absence of sensitization following thermal and electrical stimulations might have been caused by insufficient acid exposure, or because sensitization needs more time to develop.…”
Section: Discussionmentioning
confidence: 90%
“…Krarup et al . quantified normal values for sensation to mechanical, thermal, and electrical stimuli in adult healthy males both before and after acid‐induced sensitization . Earlier studies in HV report that men are more sensitive to esophageal distention after acid perfusion than women .…”
Section: Introductionmentioning
confidence: 98%